Lower Gastrointestinal Bleeding and Ischemic Colitis - Jamie R Newman; Mary Anne Cooper (Canadian Journal of Gastroenterology)
OBJECTIVE: To compare the incidence and clinical characteristics of lower gastrointestinal (LGI) bleeding due to ischemic colitis with those with LGI bleeding of other causes.